Human rights defenders as a vulnerable group included in the National Plan on Human Rights 2018-2021 - Rodríguez Gómez, Edgardo (2018)
Human rights defenders exist as a group scarcely recognized in public policies on human rights in Peru. The last national plan on human rights has included this vulnerable and diverse group in its strategic content in order to handle their problems. However, in this article the author proposes to acknowledge defenders beyond the challenges they and the state must confront: human rights defenders have a fundamental role in the consolidation of rule of law.